Analisis Kebijakan Penanganan Pengungsi Rohingya di Provinsi Aceh - Nawar, Makhisan; Muazzinah, Muazzinah; Marzaniar, Putri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This study analyzes the Rohingya refugee policy in Aceh Province using a Human Security approach. The research aims to assess the effectiveness of existing policies in protecting refugees’ rights while maintaining local social stability. Using a qualitative case study method, this study incorporates interviews with key stakeholders and analysis of secondary data. Findings indicate that current policies fall short in addressing legal enforcement, refugee empowerment, and local community acceptance. Additionally, social media reinforces polarization through the spread of stigma and hate speech. A more holistic, collaborative, and human rights-based policy approach is needed to achieve a just and sustainable long-term solution.